Analisis Rasio Likuiditas Dan Rasio Solvabilitas Dalam Mengukur Kinerja Keuangan Pt Industri Jamu Dan Farmasi Sido Muncul Tbk - Raihani Maulidina Azhar; Regina Selviyanti; Fitri Faujiah; Irwan Putra Juang Hulu; Yolanda Fasya (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
Financial performance evaluation of companies is an essential aspect for assessing and measuring overall financial position. The analysis of corporate financial performance can be conducted using financial ratios, including liquidity ratios and solvency ratios. Liquidity and solvency ratios are utilized to assess the extent to which a company can meet its financial obligations. The data used in this study is qualitative, consisting of primary data from the financial statements of PT. Sido Muncul, Tbk for the period 2023-2024, obtained from the company's official website using documentation techniques. The analysis results using Debt To Total Asset Ratio indicate that the ratio values during the period 2020-2024 consistently remained below the measurement standard threshold, i.e., less than 35%. Similarly, the analysis using Debt To Equity Ratio also shows that the ratio values during the period 2020-2024 consistently remained below the measurement standard threshold, i.e., less than 90%. Ratios below the standard indicate that the company's financial performance in meeting its obligations can be considered satisfactory, as lower ratio values signify greater assets and equity used as collateral for the company's debts.